One step lithography of polypyrrole - Acevedo, Diego Fernando (2011)
Large areas of polypyrrole (PPy) thin films deposited onto inert polymeric substrates are structured by direct laser interference patterning (DLIP). Several square millimeter areas could be produced with one single (10âns) pulse, at room temperature and atmospheric pressure. Nanometric arrays of lines (>600ânm) or grids of PPy deposited on dielectric polymers polypropilene or polypirrol (PP or PE) are fabricated by DLIP at 355ânm. The period of the lines structures, measured by white light interferometry (WLI), is 3.5âÂμm. Regular structures are analyzed using scanning electron microscope (SEM) and a focus ion beam (FIB) tomography. It is shown that only the PPy film is structured while the PP or PE substrate remains unaltered. Fourier transform infrared spectroscopy (FTIR) and UV-vis spectroscopy, permit to ensure that PPy chemical structure remains unaltered after the structuration process. The width of PPy lines can be tailored by controlling the fluence of the laser beam. Contact angle measurement shows that the wettability is affected by the structuring, making the surface more hydrophobic. The structuring technique seems to be suitable for the fabrication of PPy regular structures over various substrates.